Study on sedimentation stability of silicone oil-based magnetorheological fluids with fumed silica as additive - Yu, Long; Chen, Fei; Li, Haopeng (Frontiers in Materials, 2024)
In order to study the sedimentation stability of silicone oil-based magnetorheological fluids with fumed silica as additive, magnetorheological fluids with different mass fractions of fumed silica, particle sizes of carbonyl iron powder and viscosities of silicone oil were prepared. The sedimentation rate of magnetorheological fluids was calculated by observation method, and the zero-field viscosity of magnetorheological fluids was measured by viscometer. The results show that the sedimentation rate and viscosity of magnetorheological fluids increase gradually with the increase of the mass fraction of fumed silica. The mass fraction of fumed silica should not be constant for magnetorheological fluids, but should be determined according to the content of silicone oil in magnetorheological fluids. With the increase of average diameter of carbonyl iron powder, the sedimentation stability of magnetorheological fluids becomes worse. With the increase of viscosity of silicone oil, the sedimentation stability of magnetorheological fluids does not increase significantly. However, the high viscosity of silicone oil will result in wall hanging phenomenon, and increase the start-up difficulty of magnetorheological device. With 2.5 wt% of fumed silica for silicone oil, the magnetorheological fluids has good sedimentation stability and suitable zero-field viscosity.